Edukasi Budidaya Anggrek Bagi Kelompok Pemuda di Rasau Jaya Kubu Raya - Rafdinal Rafdinal; Dwi Gusmalawati; Surya Abi Alfariz; Venia Nur (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Orchids are plants that have been cultivated because they have high economic value. Orchid cultivation is also done to maintain its sustainability. Orchid cultivation requires special knowledge to produce good growth. This educational activity aims to provide knowledge and skills about orchid cultivation for Rasau Jaya Kubu Raya youth group. The method of implementing this activity includes preparation, implementation, and evaluation. Preparation includes coordination with partners regarding the schedule, location, tools, and materials needed. The implementation of activities consists of the delivery of material on the prospects of orchid cultivation, the stages of cultivation, demonstrations, and practices of planting and crossing orchids. Evaluation was carried out by filling out a questionnaire. The knowledge and skills of participants in this educational activity increased from 70.00% who did not know to 40% who knew and 60.00% who were very knowledgeable through the delivery of materials, demonstrations, and practices. This training was beneficial (70.00%) and inspiring (100%). Participants hope that this educational activity can be practiced by themselves and inspire them to open an orchid cultivation business.